Unemployment, Welfare, and Masculine Citizenship - Levine-Clark, M. author. aut Link
XIX, 304 p.
Keywords: This book examines how, from the late nineteenth century through the 1920s, British policymakers, welfare providers, and working-class men struggled to accommodate men's dependence on the state within understandings of masculine citizenship.